FAKTOR MATERNAL YANG BERHUBUNGAN DENGAN KEJADIAN PADA IBU HAMIL DI DAERAH URBAN - SASTRI, NEN (IKesT Muhammadiyah Palembang, 2020)
The 2015 Indonesian health profile shows that the maternal mortality rate (MMR) is 305 maternal deaths per 100,000 live births. The complications that occur are of course inseparable from the poor nutritional status of the mother and ultimately have an impact on the condition of the fetus being born (Ministry of Health, Republicof Indonesia, 2015). This study aims to determine the relationship between age, education, occupation, birth spacing, parity in pregnant women with the incidence of KEK at BPM Ellna Palembang in 2017. The research used is an observational study with a case control approach. The population in this study were all pregnant women from 1 sd 12, 2017. Case criteria are all suspected pregnant women with KEK recorded in the pregnancy register book and LILA examinatios known less than 23,5 cm. Data analysis: univariate analysis, bivariate analysis, multivariate analysis. The results of the research of pregnant women obtained a frequency distribution based on the incidence of KEK as many as 87 cases of KEK. The results of the analysis of the relationship between the age and the incidence of KEK obtained a significant value of p = 0.007 OR obtained at 3.302. Analysis of the relationship between the education with the incidence of KEK obtained a significant value of p = 0.030 OR obtained at 1.870. Analysis of the relationship between the occupation and the incidence of KEK obtained a significant value of p = 0.002 OR was obtained for 2.538. Analysis of the relationship between parity and the incidence of KEK obtained a significant value of p = 0.000 OR obtained at 2.758. Analysis of the relationship between birth spacing and the incidence of KEK obtained a significant value of p = 0.014 OR obtained at 2.359. In conclusion there is a relationship between age, education, occupation, parity, birth spacing of pregnant women and incidence of KEK. Key words: KEK in pregnant women